2013
DOI: 10.1055/s-0033-1358369
|View full text |Cite
|
Sign up to set email alerts
|

Amount of Therapy Matters in Very Early Aphasia Rehabilitation after Stroke: A Clinical Prognostic Model

Abstract: Background and Aim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…Taken together with the fact that the intensity (duration and frequency) of both intensive therapy periods were equal and different from the conventional therapy period, it is most likely that the intensity influenced RL's therapeutic outcome (alterations of the behavioural PALPA 1 and neurophysiological N400 PW amplitude). Although a large number of studies provide evidence for the efficacy of intensive treatment (e.g., Breitenstein et al, 2009;Meinzer, Rodriguez, & Gonzalez Rothi, 2012;Godecke et al, 2013;Pulvermüller et al, 2005), other studies claim that intensity does not provide an added value to therapy results (Bakheit et al, 2007;Cherney, Patterson, & Raymer, 2011;Hinckley & Carr, 2005). However, when taking a closer look at the methodology, there seems to be a difference compared to the present study concerning the actual definition of intensity and type of therapy.…”
Section: Effect Of Therapy Per Periodcontrasting
confidence: 61%
See 2 more Smart Citations
“…Taken together with the fact that the intensity (duration and frequency) of both intensive therapy periods were equal and different from the conventional therapy period, it is most likely that the intensity influenced RL's therapeutic outcome (alterations of the behavioural PALPA 1 and neurophysiological N400 PW amplitude). Although a large number of studies provide evidence for the efficacy of intensive treatment (e.g., Breitenstein et al, 2009;Meinzer, Rodriguez, & Gonzalez Rothi, 2012;Godecke et al, 2013;Pulvermüller et al, 2005), other studies claim that intensity does not provide an added value to therapy results (Bakheit et al, 2007;Cherney, Patterson, & Raymer, 2011;Hinckley & Carr, 2005). However, when taking a closer look at the methodology, there seems to be a difference compared to the present study concerning the actual definition of intensity and type of therapy.…”
Section: Effect Of Therapy Per Periodcontrasting
confidence: 61%
“…In terms of timing of therapy after stroke, language treatment seems to improve communication outcome in people with moderate to severe aphasia in both very early and chronic stages of recovery from stroke, independent of type and content of treatment (Allen et al, 2012;Corsten et al, 2007;Godecke, Hird, Lalor, Rai, & Phillips, 2012;Godecke et al, 2013). However, others have suggested that aphasia therapy might not provide added value in the acute stage, as functional communication sometimes improves equally after speech and language therapy, with regular social contacts or even without therapy (Bowen et al, 2012;Laska, Kahan, Hellblom, Murray, & von Arbin, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This investigation was prompted by research indicating that persons with acute aphasia benefit from speech and language therapy that is more intensive (Brady et al, 2012; Godecke et al, 2013; Martins et al, 2013). Although we found that an additional daily hour of CILT was feasible to implement during the two-week course of the study, there were major barriers with regard to pairing participants and scheduling the sessions.…”
Section: Discussionmentioning
confidence: 99%
“…We also hypothesized that the participants receiving CILT would show greater gains on standardized measures selected from the BDAE as compared to participants receiving usual care. These hypotheses were based on evidence suggesting that more intensive treatment would benefit participants with acute/subacute aphasia (Godecke et al, 2013; Kirmess & Maher, 2010; Martins et al, 2013). …”
mentioning
confidence: 99%